Neurodevelopmental outcome of infants without central nervous system anomalies born to symptomatic RT-PCR ZIKV positive women. - Luis Alfonso Díaz-Martínez; Mario Augusto Rojas; Luz Stella Pinilla-García; Carlos Hernán Becerra-Mojica; Luis Alfonso Pérez-Vera; Luz Ángela Gutiérrez-Sánchez; Gustavo Adolfo Contreras-García; Carol Gisela Rueda-Ordoñez; Luis Villar (Public Library of Science (PLoS), 2022)
An epidemic of Zika virus (ZIKV) infection began in Colombia in October 2015. Previous studies have identified a cause-effect relationship between fetal exposure to the ZIKV and the development of microcephaly and other central nervous system (CNS) anomalies with variable degrees of neurodevelopmental delay. Less is known about the neurodevelopmental outcome of infants without CNS anomalies born to symptomatic ZIKV RT-PCR-positive women. We aimed to compare the neurodevelopmental outcome of these infants to a control group of infants without CNS anomalies born to asymptomatic ZIKV RT-PCR negative women who did not seroconvert during pregnancy. Participating infants were categorized according to ZIKV maternal exposure. Women with symptomatology suggestive of ZIKV infection and a positive RT-PCR for ZIKV were categorized as ZIKV-exposed. Maternal controls (ZIKV unexposed) from the same geographic area were subsequently captured during the tail end of the epidemic through a partner project, the ZIKAlliance, whose aim was to determine the prevalence of ZIKV in pregnant women. Infant survivors from these two groups of pregnant women had a neurodevelopmental evaluation at 12, 18, and 24 months corrected age (CA). The ZIKV-exposed women were found to be older, had less subsidized health care, had a higher percentage of women in middle-class socioeconomic strata, had higher technical and university education, were less likely to be living with a partner, and had higher rates of pregnancy comorbidity and premature births than ZIKV unexposed women. Compared to infants born to ZIKV unexposed women (unexposed), infants born to ZIKV exposed women (exposed) were of lower gestational age and required more speech and occupational therapy services. No differences between groups were observed in the proportion of cut-off scores <70 on the Bayley-III Scale at 12, 18, and 24 months for motor, language, and cognitive domains. When a cut-off of <85 was used, a higher percentage of motor and cognitive impairment was observed in unexposed infants at 12 and 24 months CA, respectively. Median and IQR score on the Bayley-III scale showed higher scores in favor of exposed infants for motor development at 12 and 18 months CA, language at 12 months, and cognitive domain at 12, 18, and 24 months. The adjusted median and IQR compound score of the difference between exposed and unexposed was higher in favor of exposed infants at 12 to 24 months CA for motor (3.8 [95% CI 1.0 to 6.7]) and cognitive domains (10.6 [95% CI 7.3 to 13.9]). We observed no differences in the language domain (1.9 [95% CI -1.2 to 5.0]). We conclude that infants with no evidence of microcephaly or other CNS anomalies born to ZIKV-exposed women had normal neurodevelopment up to 24 months of CA, supporting an all-or-nothing effect with maternal ZIKV exposure. Long-term follow-up to evaluate school performance is required. Clinical Trial Registration: www.clinicaltrials.gov, NCT02943304.